ANALISIS PUTUSAN HAKIM PENGADILAN NEGERI SIAK DALAM PERKARA PERDATA NOMOR 37/Pdt.G/2018/PN.SAK TENTANG PENETAPAN GANTI KERUGIAN PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Maryam Khairunnisa; Rika Lestari; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This research related to the analysis of the decision of the judge of the Siak District court incivil case number 37/Pdt.G/2018/PN.Sak regarding the determination of compensation fordevelopment in the public interest. Based on this decision, there are many things that need to bestudied because they are not in accordance with the provisions of existing laws an regulations.Therefore, it is necessary to study stimulatively the first consideration of the judge in the decision ofthe Siak District court in civil case number 37/Pdt.G/2018/PN.Sak regarding the determination ofcompensation for development for the public interest.. Second, the suitability of the judge’s decisionto the theory of justice according to the Siak district court in civil case number 37/Pdt.G/2018/PN.Sakregarding the determination of compensation for development in the public interest.